Mesenchymal stem cell-derived exosomes: A novel potential therapeutic avenue for cardiac regeneration - Safari, S; Malekvandfard, F; Babashah, S; Alizadehasl, A; Sadeghizadeh, M; Motavaf, M (Cellular and Molecular Biology, 2016)
Coronary artery diseases (CADs) represent a significant cause of death worldwide. During recent decades the rate of cardiovascular mortality has been declined as a result of modern medicine and surgery. However, despite the fact that cardiac cells, including cardiomyocytes (CMCs), vascular smooth muscle cells (VSMC) and vascular endothelial cells (VEC), can be regenerated by cardiac adult stem cell, the regenerative capacity of these cells are limited and inadequate to functionally regenerate heart damaged tissue. Thus, growth reserve of the heart fails to restore the structural integrity of the myocardium after infarction and healing is associated with scar formation. An explanation for this is that cardiac reside stem cells are present throughout the infarction site but die rapidly by apoptosis. Furthermore, microenvironment surrounding the damage site is not promising for the cells survival and renewal. Hence, recent advances in the stem cell therapy have emerged as an attractive approach to replace the lost cells. In this context, mesenchymal stem cells (MSCs) has considered as one of the most promising candidates for regeneration of cardiac cells, lost upon injury. The regenerative capacity of MSCs has primarily been centered on the hypothesis that these cells would engraft, differentiate and replace damaged cardiac cells. However, experimental and clinical observations so far have failed to establish if this differentiated is considerably relevant to MSCs cardiac regenerative properties. Recent reports have suggested that these therapeutic properties, at least in part, are mediated by paracrine factors released from MSCs. This review provides a concise summary of current evidences supporting the paracrine hypothesis of MSCs. In particular, the scope of this review focuses on the role of MSC-derived exosome (MSC-EXs) as a therapeutic modality for the treatment of CADs, particularly ischemic myocardial dysfunctions.